Crónicas de una juventud emergente (Apropiación escultural para un neorrealismo social) - Noriega Armijos, Verónica (2014)
This project is focused on presenting a proposal in the sculpture field that has to do with my point of view about the problem for students to freely enter the career of their own choice. There are some important objectives for this process: - Make a research about the Mexican Muralis mand their influence on Ecuadorian arts - To investigate about the ecuadorian artists vision of the twentieth century in response to the social problems according to their time. - To explore the Ecuadorian high education: their requirements, proposals and consequences of the implantation of this new system on students who want to study at a public university. - Make surveys to determine the veracity of my sculptural proposal, the desired outcome is to develop a proposal made of clay, wich will be efficient and original.